Design of UWB antenna integrated with dual GSM functionalities and dual notches in the UWB region using single branched EBG inspired structure. Issue 10 (22nd May 2019) - Ghosh, Anumoy; Sen, Gobinda; Kumar, Mukesh; Das, Santanu
Abstract : A microstrip line fed planar monopole patch antenna is designed to provide impedance bandwidth (| S 11 | ≤ −10 dB) of 2.56–12.25 GHz, thus exhibiting ultra‐wideband (UWB) characteristic. Two metallic strips are branched symmetrically from the patch radiator to generate resonant frequencies at 0.9 and 1.9 GHz, corresponding to GSM operating frequencies. A filtering element based on electromagnetic bandgap (EBG) unit cell is placed near the feedline of the antenna to introduce two notches at 5.17 and 7.97 GHz thereby mitigating any interference from lower WLAN and X‐band satellite uplink frequencies respectively. The proposed structure has satisfactory gain at the GSM frequencies and fairly constant gain with a variation of <2 dB in its UWB operating region except at the notch bands. The radiation patterns are stable and symmetric with low cross polarisation. In order to comprehend the novelty of the proposed structure, it is compared with similar structures found in literature in terms of notch generation, achieving extra resonance outside UWB range, compactness, thickness of the substrate, and maintaining consistent gain in UWB region. A prototype of the proposed structure is fabricated and the measured results are in good agreement with the simulated results.